Environmental, Chemical and Medical Sensors (Energy, Environment, and Sustainability,, 2018)
This book covers the fundamentals of sensor technologies as well as the recent research for the development of environmental, chemical and medical sensor technologies. Chapters include current research on microflow cytometry, microfluidic devices, colorimetric sensors, and the development of low-cost optical densitometric sensors and paper based analytical devices for environmental and biomedical applications. Special focus has been given to nanotechnology and nanostructures- their fabrication, uses and utility in different fields of research such as for the design of tools for medical diagnostics, therapeutics, as well as for detection and estimation of pollutant levels in water and air quality monitoring. This book is intended as a resource for researchers working in the field of sensor development across the world. .